Wife Murder as Child’s Game: – analytical reflections on Eminem’s performative self-dramatization - Kaargaard Nielsen, Steen (Danish Yearbook of Musicology, 2007)
A key characteristic in the vocal art of American rap artist Eminem is a rather complex and unpredictable game of performative self-dramatization pinpointed in his studio recordings. The songs present the listener with autobiographical material staged in disturbing and yet fascinating audio mini-dramas coupled with a purposefully slippery interplay of various subject positions related to the artist’s three public personae: Marshall Mathers, Eminem and Slim Shady. The aim of the present article is to explore and discuss key elements in these artistic constructions of performative self-dramatization by focusing on five thematically related songs, in which the artist casts himself as father and/or husband: ‘ ’97 Bonnie and Clyde’, ‘Kim’, ‘My dad’s gone crazy’, ‘Hailie’s song’, and ‘Mockingbird’.